Public Awareness on Data: Case in Indonesian Elections and Advocating For Cybersecurity Reinforcement - Mohammad Fadil Imran; Dwi Asmoro (Universitas Sultan Ageng Tirtayasa, 2024)
The rapid pace of internet advancement necessitates heightened vigilance from internet users and the broader community to combat the pervasive adverse effects, including counterfeiting and data theft. This research aims to present a comprehensive analysis of the level of public awareness regarding data protection during the election process in Indonesia. It also explores different suggestions to enhance cyber security in the context of elections, based on previous literature analysis and current observations. Our finding shows the public has been aware regarding the security of their personal data, specifically the Population Identification Number (NIK), due to the revelation of reporting or complaints, as well as extensive verification of personal identities on political party member validation platforms. On the other hand, the issue of NIK data theft must be taken seriously by the government. As a result, this article suggests that policymakers increase public awareness by increasing digital literacy and strengthening data security regulations.